Methods for ascertaining norovirus disease burdens. Issue 11 (2nd November 2017) - Allen, David J.; Harris, John P.
ABSTRACT: Norovirus is the commonest cause of gastrointestinal disease worldwide in. Infections with norovirus occur in all age groups, however, the highest incidence is in children aged less than five years. Surveillance of norovirus is complicated because most people do not contact medical services when they are ill. Nevertheless, Public health laboratory surveillance worldwide has demonstrated the dominance of GII.4 viruses in the population. Better epidemiological surveillance and outbreak investigations, coupled with wider implementation of molecular-based laboratory diagnostics are leading to better estimates of the burden of norovirus infections as well as improved outbreak control. Recent advances in cell culture systems for norovirus and current research investigating the distribution of norovirus-associated disease in the population, for whom the disease burden is greatest, understanding host susceptibility factors, and methodologies for ascertaining cases, are important in increasing our understanding of norovirus. The key to surveillance of norovirus is allying the epidemiology with surveillance of virology. With recent advances in laboratory culture systems for norovirus, next generation sequencing technologies, improved diagnostics and measuring phenotypic characteristics of noroviruses, there are new opportunities to advance understanding of this common and important human pathogen that will help design strategies for vaccine and antiviral development, and how these might be best deployed to control norovirus infection.